Synthesis of Beta-Aminocarbonyl Compounds and Hydrazine Derivatives Using Amino- and Imino-Isocyanates - Clavette, Christian (Université d'Ottawa / University of Ottawa, 2015)
Over the past recent years, β-aminocarbonyls have been of great interest to medicinal chemists. As a practical method to obtain these moieties, alkene aminocarbonylation, accounting for the formation of a C-N and a C-C bond, has been the subject of limited research efforts (very specific intramolecular metal-catalyzed variants have been reported). Direct aminocarbonylation of alkenes constitutes a challenging and an important potential innovation in the synthesis of β-aminocarbonyls such as β-amino acids. The research efforts described in the present thesis have been primarily directed towards the development of concerted pathways for the amination of alkenes using hydrazine derivatives as bifunctional reagents. Building on our previous report on the reactivity of hydrazides, progress on the aminocarbonylation of alkenes along with the synthetic scope of this reactivity are herein provided. Therefore, the first part of the present thesis (Chapter 2) focuses primarily on the development of thermolytic conditions for the intramolecular aminocarbonylation of alkenes using amino-isocyanates. Alongside, development of imino-isocyanates have provided complementary synthetic tools for aminocarbonylation. The second part (Chapter 3) describes the work accomplished towards intermolecular aminocarbonylation of alkenes and the synthesis of complex azomethine imine products (Chapter 3). Finally, the last part of the discussion (Chapter 4) will be on the development of new hydrazide reagents for the intramolecular Cope-type hydroamination of alkenes. In doing so, description of the synthetic utility of amino-isocyanates as amphoteric reagents for cascade reactions and heterocyclic synthesis will be provided.
Keywords: Aminocarbonylation; Hydrazide; Hydrazine; Amino-isocyanate; Imino-isocyanate; Blocked isocyanate; Heterocyclic synthesis; Beta aminocarbonyl; Peptidomimetic